The The Integration of Mathematics Reading Activities into Mathematics Instruction - Selvi Amelia Rahmawati, Rr.; Sopandi, Wahyu; Turmudi, Turmudi; Surya, Yohanes; Rahmat Riyadi, Arie (IJORER : International Journal of Recent Educational Research, 2026)
Mathematics reading, encompassing the comprehension of mathematical texts, symbols, and visual representations, is a critical yet underexplored dimension of numeracy literacy. Many students struggle to connect textual information with mathematical concepts, leading to reduced problem-solving performance, especially in word problems under the National Curriculum. This study aims to examine the effectiveness, types, and impacts of mathematics reading activities, as well as the instructional strategies and classroom conditions that support their integration. Employing a Systematic Literature Review (SLR) of 19 Scopus-indexed empirical studies (2019–2024) using the PRISMA framework, the analysis highlights that activities such as close reading, text-to-symbol transformation, questioning strategies, and digital tools significantly enhance contextual understanding, problem modeling, and complex problem-solving skills. Among the identified approaches, the Gasing Method emphasizing gradual transition from concrete to abstract understanding, mental arithmetic, and intensive reading of problem texts aligns strongly with the needs of numeracy literacy development. Integration is most successful when supported by scaffolding, metacognitive strategies, and a literacy-rich learning environment. These findings suggest that embedding structured mathematics reading activities, including those within the Gasing Method framework, can foster literate, confident, and capable problem-solvers in elementary education while supporting the National Curriculum’s emphasis on contextual and critical thinking